THE ROLE AND PLACE OF TECHNOLOGY IN THE FORMATION OF METHODOLOGICAL COMPETENCE OF FUTURE TEACHERS - Kaskatayeva Bakhytkul; Yessengaliev Sanat (Theoretical Hypotheses and Empirical Results, 2023)
Socio-economic changes in the country and information development throughout the civilized world, changing social demand for professional training of school teachers, require a review of the traditionally established education system, methods and technologies. Therefore, in the system of professional training in higher educational institutions, an urgent problem is the introduction of new educational technologies and the formation of high-level students ' skills to widely use information technology tools in teaching activities. In a modern pedagogical University, it is important to create a culture of students ' choice and application of teaching tools and technologies in the professional training of teachers. Professional training of future teachers was formed in the logic of the competence approach. Since the competence approach recognizes the need to create conditions for the creation of personal guidelines and training content, the activation of independent educational activities. Lectures and practical classes in higher educational institutions should be provided with modern technologies that form the professional orientation and technological training of students, i.e. the ability to choose pedagogical technologies in future activities and apply them in practice. Since pedagogical technologies have the ability to form the methodological competence of the future teacher. For a long time, "technology" was not used in the conceptual apparatus of pedagogy. The exact essence of the technology "teaching about skill" was closer to the tasks of pedagogy (description, interpretation, forecasting, design of pedagogical processes), but it was used in the technical sphere.